2016
DOI: 10.1167/iovs.15-17894
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Corneal Graft Rejection in the Setting of Previous Corneal Herpes Simplex Virus (HSV)-1 Infection

Abstract: PurposeThe “high-risk phenotype” of corneal graft recipients is considered to be related to preexisting vascularization such as that associated with herpes simplex virus-1 (HSV-1) keratitis (HSK). The purpose of this study was to investigate the immunologic mechanisms underlying accelerated corneal graft rejection using a mouse model of HSK.MethodsHerpes simplex virus type 1 keratitis was induced in BALB/c mice. Syngeneic and allogeneic (C57BL/6 mice) corneal grafts were performed in mice with HSK at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…We showed that syngeneic corneal grafts (that normally induce only very mild and transient corneal inflammation) induced more prolonged and robust inflammation when placed on KOS HSV-1 infected corneal bed with subclinical inflammation at 28-34 dpi. Our current data agree with our previous report in that opacity in syngeneic corneal grafts placed on previously HSV-1 KOS infected corneas with subclinical inflammation did not reach a sustained opacity score of 12 (opacity of 3 in each quadrant of the graft) that would be considered to be a rejected or failed corneal graft [28]. However, the inflammation in syngeneic grafts placed on previously HSV-1 infected corneal beds was significant, and would be unacceptable in a human graft.…”
Section: Discussionsupporting
confidence: 92%
“…We showed that syngeneic corneal grafts (that normally induce only very mild and transient corneal inflammation) induced more prolonged and robust inflammation when placed on KOS HSV-1 infected corneal bed with subclinical inflammation at 28-34 dpi. Our current data agree with our previous report in that opacity in syngeneic corneal grafts placed on previously HSV-1 KOS infected corneas with subclinical inflammation did not reach a sustained opacity score of 12 (opacity of 3 in each quadrant of the graft) that would be considered to be a rejected or failed corneal graft [28]. However, the inflammation in syngeneic grafts placed on previously HSV-1 infected corneal beds was significant, and would be unacceptable in a human graft.…”
Section: Discussionsupporting
confidence: 92%
“…Timely recognition and management is required to prevent the recurrence of HSV‐related inflammation and graft rejection. A study in animals showed that both innate and adaptive immune mechanisms associated with anti‐HSV CD4 T‐cell response play a significant role . Most of the dissolved grafts were related to recurrence, showing the importance of taking appropriate postoperative measures to prevent recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…showed that both innate and adaptive immune mechanisms associated with anti-HSV CD4 T-cell response play a significant role. 24 Most of the dissolved grafts were related to recurrence, showing the importance of taking appropriate postoperative measures to prevent recurrence. It is recommended to continue taking oral antiviral drugs after surgery, but our patients failed to adhere to the treatment programme.…”
Section: Hsv-related Inflammation and Graft Rejection A Study In Animentioning
confidence: 99%
“…but were significantly decreased by 14 days in the PEDF+DHA-treated group, supporting our hypothesis that this biphasic response, which shows a faster resolution of inflammation in the PEDF+DHA-treated group, also may partially explain the increased nerve regeneration and recovery of sensitivity we observed. Recent work has shown that cornea-graft rejection in a mouse model of HSV-1 keratitis depends on the presence of CD4+ T cells (Kuffova et al, 2016). …”
Section: Discussionmentioning
confidence: 99%